ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN MINAT PEMANFAATAN APLIKASI JAMSOSTEK MOBILE DI BPJS KETENAGAKERJAAN CABANG BALI DENPASAR - Januraga, Pande Putu; Devi, Ade Dwita Nia Sita (ARCHIVE OF COMMUNITY HEALTH, 2024)
Jamsostek Mobile (JMO) application is an application that was launched by BPJS Ketenagakerjaan to facilitate the administrative activities for the BP Jamsostek participants. Utilization of the JMO application as of 2022, which has only reached 57.65%, this is still not in accordance with the target set by BPJS Ketenagakerjaan Branch Bali Denpasar which is 100%. The study was a quantitative study with cross-sectional method. The sample of this research are 137 BP Jamsostek participants that selected based on Consecutive sampling. This research has been conducted during March-May 2023. The data collection was obtained using questionnaire. The data analysis use univariable and bivariable analysis. The result of this study showed that the proportion of participants with interest in continuing to use the Jamsostek Mobile Application was 72,67 %. This research also showed that variable perceived usefulness, perceived ease of use, perceived credibility and amount of information correlated with interest in continuing to use the Jamsostek Mobile Application (behavioral intention to use) (p<0.05). BPJS Ketenagakerjaan should continue to socialize and support participant in using the Jamsostek Mobile application to improve the interest of participant in using the applicatioin continously. Keywords:  Jamsostek Mobile Application, BPJS Ketenagakerjaan, Technology Acceptance Model, Perceived, Behavioral Intention to Use